Cerebral Protection during Controlled Hypoperfusion in a Piglet Model: Comparison of Moderate (25°C) versus Deep (18°C) Hypothermia at Various Flow Rates Using Intraoperative Measurements and Ex vivo Investigation - Walther, Thomas; Dhein, Stefan; Ullmann, Cris; Schneider, Katja; Bilz, Thomas; Rastan, Ardawan; Garbade, Jens; Falk, Volkmar; Emrich, Fabian C.; Muth, Petra; Mohr, Friedrich W.; Kostelka, Martin (The Thoracic and Cardiovascular Surgeon, 2013)
Background During surgical correction of complex cardiac anomalies, some degree of hypoperfusion may be required. The aim of this study was to evaluate the effectiveness and safety of controlled cerebral hypoperfusion at moderate (25°C) versus deep (18°C) hypothermia.Methods In this study, 56 female piglets (9.4 ± 0.8 kg, 3–4 weeks old) received cardiopulmonary bypass (CPB) at 25, 50, or 100% of the standard flow rate for 60 minutes of cardioplegic cardiac arrest. Body temperature was kept at 18, 25, and 37°C. Routine hemodynamic and functional parameters were measured online until 4 hours of reperfusion. Immunohistology was used to quantify heat shock protein 70 (HSP70) and nitrotyrosine (NO-Tyr) levels in the hippocampus; high-performance liquid chromatography was used to quantify jugular venous blood malondialdehyde (MDA) levels.Results Reduced CPB flow led to significant reduction of mean arterial pressure by 79%, reduction of jugular venous oxygen saturation (SvO2) by 47%, reduction of carotid blood flow by 92%, and increase of serum lactate by 350%. All these changes were significantly enhanced in the 37°C versus the 25 and the 18°C groups. Regional oxygen saturation (rSO2) was significantly reduced in the 37°C low flow groups. HSP70, NO-Tyr, and MDA were increased in the 25 and 50% flow groups (p < 0.05). There was a significant correlation between rSO2 and SvO2 (r = 0.61) and between SvO2 and HSP70 (r = − 0.72).Conclusions Reduction in global blood flow during CPB leads to comparable biochemical changes in the hippocampus at 25 and 18°C. Regional oxygenation saturation, SvO2, and HSP70 are important parameters to evaluate the efficacy of further anti-ischemic therapies during surgical corrections.
Keywords: brain protection; neuropsychological deficit; extracorporeal circulation; cardiac surgery